THE USE OF GROUP INVESTIGATION TECHNIQUE IN TEACHING SPEAKING NEWS ITEM TEXT FOR THE TENTH GRADERS OF SMA NEGERI 3 SIDOARJO (RETAIN, 2013)
dan Kusumarasdyati S1- English Education, Language and Art Faculty, Surabaya State University Abstract Based on the standard competence of English subject for senior high school, speaking is one of the skills that should be mastered by the students. But, speaking English is often considered as something frighten faced by some Indonesia students. Some students are still afraid to make mistake and feel depressed in speaking activity. Those problems occur because the teachers do not know much about the speaking techniques and the students are rarely given chance to practice their speaking. To overcome those problems, the teacher in SMAN 3 Sidoarjo chooses one of cooperative learning techniques and it had been implemented well in her school, it is a group investigation technique. Group investigation is a general classroom-organization plan in which students work in a small group using group discussion, cooperative inquiry, planning and projects. The students are divided into two to six members group then they choose topic from a unit being learned by the students. This study was conducted using qualitative method design. The researcher observed the activities in the classroom during teaching and learning process. The data of the study are from the result of observation that was obtained through observation checklist and field notes, and also from the result of interview guideline. The results of observation showed that the group investigation technique can run well during the teaching and learning process. From the results of interview was found that the group investigation is effective to be used in speaking news item text. The students enjoy joining the lesson. Thus, the implementation of group investigation had improved the students’ mastery in understanding news item text and speaking skill. Keywords: group investigation, speaking activity, news item text.